Modulation of the cardiac sodium/bicarbonate cotransporter by the renin angiotensin aldosterone system: pathophysiological consequences - De Giusti, Verónica C.; Ciancio, María C.; Orlowski, Alejandro; Aiello, Ernesto A. (Frontiers in Physiology, 2014)
The sodium/bicarbonate cotransporter (NBC) is one of the major alkalinizing mechanisms in the cardiomyocytes. It has been demonstrated the existence of at least two functional isoforms, one that promotes the co-influx of 1 molecule of Na+ per 1 molecule of HCO3- (electroneutral isoform; NBCn1) and the other one that generates the co-influx of 1 molecule of Na+ per 2 molecules of HCO3- (electrogenic isoform; NBCe1). Both isoforms are important to maintain intracellular pH (pHi) and sodium concentration ([Na+]i). In addition, NBCe1 generates an anionic repolarizing current that modulates the action potential duration (APD). The renin-angiotensin-aldosterone system (RAAS) is implicated in the modulation of almost all physiological cardiac functions and is also involved in the development and progression of cardiac diseases. It was reported that angiotensin II (Ang II) exhibits an opposite effect on NBC isoforms: it activates NBCn1 and inhibits NBCe1. The activation of NBCn1 leads to an increase in pHi and [Na+]i, which indirectly, due to the stimulation of reverse mode of the Na+/Ca2+ exchanger (NCX), conduces to an increase in the intracellular Ca2+ concentration. On the other hand, the inhibition of NBCe1 generates an APD prolongation, potentially representing a risk of arrhythmias. In the last years, the potentially altered NBC function in pathological scenarios, as cardiac hypertrophy and ischemia-reperfusion, has raised increasing interest among investigators. This review attempts to draw the attention on the relevant regulation of NBC activity by RAAS, since it modulates pHi and [Na+]i, which are involved in the development of cardiac hypertrophy, the damage produced by ischemia-reperfusion and the generation of arrhythmic events, suggesting a potential role of NBC in cardiac diseases.